Compliance to infection-preventing measures in colorectal surgery – a word of caution. (1st June 2022) - Deslarzes, P; Jurt, J; Hübner, M; Demartines, N; Grass, F
Abstract: Objective: The success of a colorectal surgical site infection (SSI) preventing bundle is dependent on compliance to individual infection-preventing measures. The present study aimed to assess whether challenging circumstances may affect bundle compliance. Methods: Retrospective analysis including consecutive patients undergoing colorectal surgery and appendectomy between November 2018 and October 2020, after implementation of an evidence-based SSI-preventing care bundle. Bundle items were antibiotic administration, disinfection, core temperature control, glove change, intra-abdominal lavage and drain placement according to pre-defined standards. Compliance to each item was assessed according to surgical duration, patient age and time of surgery. Results: Over the study period, 463 patients underwent appendectomy, 458 patients colonic surgery and 98 patients rectal resections. Compliance to intraabdominal lavage standards decreased significantly with surgical duration of colonic resections (88% for surgeries lasting <90 minutes vs. 56% for surgeries lasting > 180 minutes), while similar decreasing compliance patterns were observed regarding intraabdominal drain placement (86% vs. 68%) and core temperature control (64% vs. 57%, all p>0.05) with long lasting procedures. Compliance to antibiotic timing and glove change recommendations was higher in patients undergoing day-time colectomies (08 h and 16 h) compared to patients operated on during night shifts (0h-08 h, 93% vs. 69% and 87% vs. 58%, respectively, both p<0.05). Specific compliance patterns were not observed in patients undergoing appendectomy or rectal surgery. Furthermore, patient age had no impact on bundle compliance. Conclusion: The present study revealed decreasing compliance to several infection-preventing bundle items with increasing surgical duration and during night shifts. This may contribute to worse outcomes in these challenging settings but may be a point of attention that can be corrected.